The comparison of probiotic monocultures influence on organochlorine pesticides changes in fermented beverages from cow and goat milk during cold storage - Agata Witczak, Agata (Array, 2019)
The effect of selected probiotic monocultures addition as a method of organochlorine pesticides (OCP) residues reduction in fermented beverages manufactured from cow and goat milk during cold storage was examined. Supplementation of traditional yogurt starter by single monoculture or a mixture of two monocultures has resulted in a decrease of OCPs in products during cold storage. Extension of the cold storage period up to 14 days resulted in further losses in the content of the analysed compounds. Regardless of the milk type used for beverage production, beverages prepared from the mixture of two monocultures (Lb. acidophilus LA-5 and Bifidobacterium BB-12) showed significantly greater decrease of pesticides content in comparison to beverages containing only LA-5. The maximum decrease (from 5.39 % to 20.7 %) in OCP was determined during the 14-day cold storage, and was few percent higher in beverages manufactured from goat milk.